Interannual to interdecadal variability of winter and summer southern African rainfall, and their teleconnections. Issue 11 (9th June 2016) - Dieppois, Bastien; Pohl, Benjamin; Rouault, Mathieu; New, Mark; Lawler, Damian; Keenlyside, Noel
Abstract: This study examines for the first time the changing characteristics of summer and winter southern African rainfall and their teleconnections with large‐scale climate through the dominant time scales of variability. As determined by wavelet analysis, the austral summer and winter rainfall indices exhibit three significant time scales of variability over the twentieth century: interdecadal (15–28 years), quasi‐decadal (8–13 years), and interannual (2–8 years). Teleconnections with global sea surface temperature and atmospheric circulation anomalies are established here but are different for each time scale. Tropical/subtropical teleconnections emerge as the main driver of austral summer rainfall variability. Thus, shifts in the Walker circulation are linked to the El Niño–Southern Oscillation (ENSO) and, at decadal time scales, to decadal ENSO‐like patterns related to the Pacific Decadal Oscillation and the Interdecadal Pacific Oscillation. These global changes in the upper zonal circulation interact with asymmetric ocean‐atmospheric conditions between the South Atlantic and South Indian Oceans; together, these lead to a shift in the South Indian Convergence Zone and a modulation of the development of convective rain‐bearing systems over southern Africa in summer. Such regional changes, embedded in quasi‐annular geopotential patterns, consist of easterly moisture fluxes from the South Indian High, which dominate southerly moisture fluxes from the South Atlantic High. Austral winter rainfall variability is more influenced by midlatitude atmospheric variability, in particular the Southern Annular Mode. The rainfall changes in the southwestern regions of southern Africa are determined by asymmetrical changes in the midlatitude westerlies between the Atlantic and Indian Oceans. Key Points: Three time scales of summer and winter southern African rainfall variability are identified Tropical/subtropical teleconnections are related to summer rainfall variability Winter rainfall variability is influenced by the midlatitude atmospheric dynamics